Frequency of rs2228570 single nucleotide polymorphism of Vitamin-D Receptor (VDR) gene among the Kazakh ethnic group - Protas, V.V.; Pogossyan, G.P.; Li, K.G.; Danilenko, M.P. (Fundamental and Experimental Biology, 2023)
The article presents the results of the study of vitamin D receptor (VDR) gene rs2228570 single nucleotide polymorphism (SNP) genotypes and individual alleles frequency among the Kazakh ethnic group representatives living in the Karaganda region. This SNP was determined by real-time polymerase chain reaction using TaqMan technology. The study relevance is due to the fact that genetic variations in rs2228570 affect the synthesis of the VDR protein and its activity as a transcription factor that regulates the expression of other genes. This mechanism determines the association of individual rs2228570 genotypes or alleles with susceptibility, course, and outcomes of various diseases. The polymorphism frequency may be depending on ethnicity. According to the study results, the most common genotypes of rs2228570 SNP among the Kazakhs were AG (32.8 %) and GG (25.2 %). The rarest are homozygotes TT (1.7 %) and CC (0.8 %). The frequency of all rs2228570 alleles was detected simultaneously in the present study for the first time. G became the predominant allele (51.3 %), less common was A (31.0 %), and the C and T alleles were the rarest (11.8 % and 5.9 %, respectively). The potential value of this SNP further study as a possible factor influencing the body’s susceptibility to various diseases, including COVID-19, is shown.